The Evolution of Human-Earth Relationships in Southern Shaanxi during the Neolithic Period - Wang, Cong (Technium Social Sciences Journal, 2025)
The article explores the human-earth relationship in the Neolithic period in southern Shaanxi, especially the interrelationship between the land-use pattern, the cultural distribution range, and the evolution of the local natural environment, in terms of the size and shape of the settlement sites of the archaeological cultures, and the characteristics of the assemblage of the production tools. The results show that the land-use patterns responded to by the archaeological cultures in southern Shaanxi within the Neolithic period are consistent, the cultural distribution range is affected by climate change, and the distribution density is affected by the geographic environment. Under the condition of small changes in the overall natural environment, there is no obvious change in the shape of production tools and land use patterns within each culture, and the changes in microclimate within the southern Shaanxi region affect the distribution of the archaeological cultures as well as the geographic environment of the southern Shaanxi region affects the size of the distribution density of the cultures.